Water in the Supra-Subduction-Zone Mantle of the Mariana-Izu-Bonin Forearc: Constraints From Peridotitic Orthopyroxene - Gose, Jürgen; Schmädicke, Esther (Geochemistry Geophysics Geosystems, 2021)
Orthopyroxene was analyzed as a proxy for water supra-subduction-zone peridotite by polarized infrared radiation. Samples from Conical and Torishima seamounts, Mariana-Izu-Bonin forearc (ODP-Leg 125), have very similar average H2O contents of 215 ppm (range: 122–363 ppm; Conical) and 191 ppm (range: 116–292 ppm; Torishima). Conical peridotite equilibrated at lower temperature (760°C) and oxygen fugacity (ΔlogFMQ −0.65) than samples from Torishima (830°C; ΔlogFMQ +0.33). The degree of partial melting is almost identical for the two sites (18% and 20%). The H2O concentrations are considerably higher compared to samples from the Bismarck forearc (31–92 ppm; Tollan and Hermann, 2019). Instead, the average values resemble those of peridotitic orthopyroxene from MOR settings. The measured H2O contents by far exceed values expected for residual peridotite. This implies that secondary uptake of water must have occurred after melt-extraction but prior to exhumation to shallow crustal levels. Most likely, re-equilibration took place at c. 50 km depth. As indicated by elemental correlations and/or enhanced contents, the secondary fluid(s) must have been enriched in B, K, Li, and Sr. The boron contents of orthopyroxene are c. 10 times higher those in MOR samples. These findings suggest that peridotite from Conical and Torishima seamounts was presumably infiltrated by fluid generated by dehydration reactions in a subducting plate. The elemental spectrum points to two source lithologies: (i) serpentinite (liberation of B) and metasediments (liberation of K, Li, and Sr). The varying H2O contents point to heterogeneous fluid supply suggesting that fluid infiltration was not pervasive.
CRIS-Team Scopus Importer:2021-05-07
Keywords: : mantle wedge; Mariana-Izu-Bonin forearc; orthopyroxene; peridotite; water